Pricing multi-asset financial derivatives with time-dependent parameters—Lie algebraic approach - C. F. Lo; C. H. Hui (International Journal of Mathematics and Mathematical Sciences)
We present a Lie algebraic technique for the valuation of multi-asset financial derivatives with time-dependent parameters. Exploiting the dynamical symmetry of the pricing partial differential equations of the financial derivatives, the new method enables us to derive analytical closed-form pricing formulae very straightforwardly. We believe that this new approach will provide an efficient and easy-to-use method for the valuation of financial derivatives.